Rho-kinase activity is upregulated in the skeletal muscle of aged exercised rats - Muñoz, Vitor Rosetto (2019)
There is a gap in the knowledge regarding the regulation of glucose uptake in skeletal muscle during the development of insulin resistance in the elderly. Rho-Kinase (Rock) signaling has been demonstrated as a crucial mechanism related to glucose metabolism and insulin sensitivity in skeletal muscle. This kinase is involved in the insulin receptor substrate 1 (IRS1) phosphorylation, leading to glucose uptake stimulation in the skeletal muscle; however, the mechanisms elucidating the role of Rock regulation in the context of advanced ages are still limited. In this study, we submitted old Fischer 344 rats to short-term treadmill physical exercise protocol (5 days) and evaluated the glucose tolerance and proteins involved with Rock/insulin signaling in the skeletal muscle. Compared to young rats, the old rats showed glucose intolerance, hyperinsulinemia, and decreased phosphorylation in the proteins related to the insulin signaling pathway in the skeletal muscle, without changes in body mass and adiposity. Otherwise, when these rats were submitted to physical exercise, it was found decreased fasting glucose, higher glucose tolerance, decreased insulinemia, and upregulation of Rock2/pIRS1/pAkt/pGSK3β/GLUT4 pathway in the skeletal muscle. In summary, the aging process did not change Rock signaling, but the physical exercise was able to increase Rock2 content and insulin signaling pathway in the skeletal muscle. This finding suggests the benefic role of physical exercise to advanced ages, promoting insulin-sensitive effects with Rho-kinase contribution.